1996
DOI: 10.1128/jb.178.7.2005-2009.1996
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and interaction of nitrate and nitrite reduction in Staphylococcus carnosus

Abstract: Staphylococcus carnosus reduces nitrate to ammonia in two steps. (i) Nitrate was taken up and reduced to nitrite, and nitrite was subsequently excreted. (ii) After depletion of nitrate, the accumulated nitrite was imported and reduced to ammonia, which again accumulated in the medium. The localization, energy gain, and induction of the nitrate and nitrite reductases in S. carnosus were characterized. Nitrate reductase seems to be a membrane-bound enzyme involved in respiratory energy conservation, whereas nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
77
1
8

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 38 publications
6
77
1
8
Order By: Relevance
“…In the presence of 2 mM nitrate or 1 mM nitrite, growth of the ⌬nreABC strains was slightly decreased under reduced oxygen tension in BM broth (data not shown). In S. carnosus wild type, the presence of higher nitrate concentrations (25 mM) under anoxic conditions resulted in a higher growth yield (23). During anoxic growth on BM agar plates with 20 mM nitrate, S. aureus SA113 wild type and the complemented mutant formed significantly larger colonies than the nreABC mutant, which displayed a small-colony phenotype under these conditions (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the presence of 2 mM nitrate or 1 mM nitrite, growth of the ⌬nreABC strains was slightly decreased under reduced oxygen tension in BM broth (data not shown). In S. carnosus wild type, the presence of higher nitrate concentrations (25 mM) under anoxic conditions resulted in a higher growth yield (23). During anoxic growth on BM agar plates with 20 mM nitrate, S. aureus SA113 wild type and the complemented mutant formed significantly larger colonies than the nreABC mutant, which displayed a small-colony phenotype under these conditions (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Nitrate (NO 3 Ϫ ) and nitrite (NO 2 Ϫ ) can be used as terminal electron acceptors under anaerobic conditions. In the foodgrade species Staphylococcus carnosus, used as a starter culture in the production of raw fermented sausages, the membranebound respiratory nitrate reductase, NarGHI, generates nitrite, which is further reduced to ammonia by a cytoplasmic NADH-dependent nitrite reductase encoded by the nirBD genes (23,24,26). In contrast to nitrate reduction, nitrite dissimilation is not coupled to the generation of a proton motive force and, hence, is not a respiratory pathway.…”
mentioning
confidence: 99%
“…The absence of oxygen and the presence of nitrate and/or nitrite induce nitrate reductase and nitrite reductase activities. Nitrite reduction is inhibited by nitrate and by high concentrations of nitrite (Ն10 mM), whereas nitrate reduction is not influenced by nitrite and ammonia (19).…”
mentioning
confidence: 99%
“…The absence of oxygen and the presence of nitrate and/or nitrite induce nitrate reductase and nitrite reductase activities. Nitrite reduction is inhibited by nitrate and by high concentrations of nitrite (Ն10 mM), whereas nitrate reduction is not influenced by nitrite and ammonia (19).Although the amino acid sequences of the S. carnosus nitrate reductase and nitrite reductase enzymes are similar to those of the corresponding Escherichia coli proteins, we have found evidence that the regulatory proteins and operator sequences differ (21,24).In E. coli, expression from the nir promoter (P nir ) is dependent both on FNR (fumarate and nitrate reductase regulation) and on NarL or NarP (36, 37). Recently, Browning et al (7) have shown that P nir is repressed by three DNA binding proteins, i.e., Fis (factor for inversion stimulation), integration host factor (IHF), and H-NS (histone-like nucleoid structuring protein), and that NarL and NarP can relieve IHF-and Fismediated repression but are unable to counteract H-NS-mediated repression.…”
mentioning
confidence: 99%
“…As an apathogenic organism, S. carnosus is also widely used as a Gram-positive recipient strain for molecular cloning (Gotz, 1990;Halfmann et al, 1993;Ayora & Gotz, 1994;Connolly et al, 1994;Wieland et al, 1994 ;Heilmann et al, 1996 ;Neubauer & Gotz, 1996), as well as for the production of heterologous proteins (Demleitner & Gotz, 1994;Pschorr et al, 1994;Samuelson et al, 1995;Strauss & Gotz, 1996;Robert et al, 1996;Thumm & Gotz, 1997;Liljeqvist et R. Pantiieek and others Rosenstein et al, 1992;Wieland et al, 1995;Bruckner & Gotz, 1996;Bruckner, 1997) were developed.…”
mentioning
confidence: 99%